2018
DOI: 10.3390/brainsci8080141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Administration of Nickel on Affective and Cognitive Behavior in Male and Female Rats: Possible Implication of Oxidative Stress Pathway

Abstract: Nickel (Ni) toxicity has been reported to produce biochemical and behavioral dysfunction. The present study was undertaken to examine whether Ni chronic administration can induce alterations of affective and cognitive behavior and oxidative stress in male and female rats. Twenty-four rats, for each gender, divided into control and three test groups (n = 6), were injected intraperitoneally with saline (0.9% NaCl) or NiCl2 (0.25 mg/kg, 0.5 mg/kg and 1 mg/kg) for 8 weeks. After treatment period, animals were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 97 publications
5
21
0
Order By: Relevance
“…Another central effect that we highlighted was the effect of Ni on memory function. Our results also revealed that the chronic administration of Ni causes learning and memory deficits in the MWM test, confirming our previous findings [13]. These results were parallel to a previous report on the association of Ni exposure with memory impairment assessed in the MWM [10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another central effect that we highlighted was the effect of Ni on memory function. Our results also revealed that the chronic administration of Ni causes learning and memory deficits in the MWM test, confirming our previous findings [13]. These results were parallel to a previous report on the association of Ni exposure with memory impairment assessed in the MWM [10].…”
Section: Discussionsupporting
confidence: 92%
“…Ni is known to disrupt the pro-/antioxidant balance in the cells [13], which may precede neurobehavioral disorders. Our previous study showed that chronic Ni exposure induced depression-like, anxiety-like, memory deficit, and alterations in OS markers in the hippocampus [13], a crucial brain region in learning, memory processes, and emotion regulation [14,15]. These effects are similar to those induced by other heavy metals such as Copper(Cu), Cadmium(Cd) and Aluminum(Al) [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…A dose of 1 mg/kg CuCl 2 showed maximum anxiety-like and depression-like symptoms as compared to controls. The Cu effects observed in our study are similar to numerous heavy metals (Cd, Al and Ni)[7] [8][10].…”
supporting
confidence: 78%
“…Exposure to metals from environment, which are highly neurotoxic and have no other biological functions, such as aluminum (Al), lead (Pb) and cadmium (Cd), has long been debated as a potential environmental risk factor for mood disorders [7] [8]. However, nowadays, people are mainly focusing on biologically important metals such as copper (Cu), because their imbalance is related to a profound physiological alteration including the central nervous system (CNS) [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial learning and memory were impaired in males at the top dose only. There were associated changes in enzymes involved in antioxidant response and evidence of oxidative stress, which the authors consider may be the causative mechanism (Lamtai et al., 2018). Further evidence of oxidative stress is evident from a report that nickel causes elevation of metallothionein and oxidative stress in mouse brain (Sadauskiene et al., 2013).…”
Section: Assessmentmentioning
confidence: 99%